Belagenpumatucel-L for the treatment of non-small cell lung cancer. (September 2015) - Rijavec, Erika; Biello, Federica; Genova, Carlo; Barletta, Giulia; Maggioni, Claudia; Dal Bello, Maria Giovanna; Coco, Simona; Truini, Anna; Vanni, Irene; Alama, Angela; Beltramini, Sabrina; Grassi, Maria Attilia; et al.
<x xml:space="preserve">Abstract</x> Introduction: Immunotherapy has become a promising approach for the treatment of NSCLC. In order to stimulate the host immune system against tumour antigens, several cancer vaccines have been generated and evaluated. <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Belagenpumatucel-L&logicalOpe1=OR&field2=articletitle&text2=Belagenpumatucel-L&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Belagenpumatucel-L is a whole tumour cell vaccine expressing the antisense strand of the TGF-β2 gene. Areas covered: The purpose of this article is to review the most relevant findings of clinical trials testing belagenpumatucel-L in advanced NSCLC patients. Expert opinion: Although the Phase III trial investigating belagenpumatucel-L in stage III/IV patients did not meet its primary end point, a survival benefit was observed in several subgroups of patients. Further studies are needed in order to select patients who may benefit from this vaccine.